The Letter of Aristeas: 'Aristeas to Philocrates' or 'On the Translation of the Law of the Jews' - Wright, Benjamin G. (Commentaries on Early Jewish Literature (CEJL), 2015)
In modern scholarship, there has been no fully fledged commentary written on the Letter of Aristeas, an important work of Hellenistic Judaism in Alexandria, which contains the earliest version of the translation of the Septuagint. This volume fills that gap. The book will be of relevance to anyone interested in Hellenistic Judaism, the Septuagint, the ancient Jewish community in Alexandria or ancient Jewish paideia.